Evaluating the Efficacy of the Er,Cr:YSGG Fractional Laser Before Treatment With Triamcinolone NN Ointment in Oral Lichen Planus Lesions: Lichen Planus and Laser Assisted Drug Delivery System - khalighi, Hamid Reza; Anbari, Fahimeh; Mojahedi, Seyed Masoud; Forouzani, Gelareh (Journal of Lasers in Medical Sciences, 2022)
Introduction: It has been demonstrated that laser technology can enhance topical drug absorption. This study aimed to determine the effects of Er, Cr: YSGG laser radiation before the application of topical corticosteroids in the healing of oral lichen planus. Methods: In this double-blind split-mouth clinical trial, 32 lesions were chosen from eight patients affected by oral lichen planus (OLP). The oral lesions were randomly categorized into two groups. The first group had topical treatment with triamcinolone NN ointment and the second group had laser radiation (Er,Cr:YSGG) for eight weeks before starting the ointment. For each lesion, the irritating level based on the VAS score, the lesion level based on the Thongprasom scale score, and the healing time were measured, and the collected data were analyzed by the Friedman test and the Wilcoxon’s statistical test. Results: The mean healing time based on the verbal analog scale (VAS) score was not significantly different between the two treatment groups (P>0.05). The mean healing time based on Thongprasom scale scores did not show any significant difference between the two treatment groups (P>0.05). Conclusion: The application of the Er,Cr:YSGG laser before treatment with triamcinolone NN ointment did not show any advantage for the average healing time compared to a medicine regimen with only triamcinolone NN ointment. Doi:10.34172/jlms.2022.23.